Efektivitas Pemberian Jus Buah Tomat (Lycopersacum esculentum m.) dengan Jus Buah Jambu Biji Merah (Psidium guajava l.) terhadap Penurunan Kadar LDL pada Tikus Putih Jantan Galur Wistar (Rattus norvegicus l.) yang Diinduksi Diet Tinggi Lemak - Namora Harahap, Asra Dewita; Hariaji, Ilham (Buletin Farmatera, 2018)
Introduction: Cardiovascular disease is the number one cause of death globally, abnormal levels of LDL are often linked to risk factors for cardiovascular disease. Tomato juice (Lycopersacum esculentum M.) and red guava (Psidium guajava L.) contain lycopene which is high enough antioxidant to prevent oxidation of LDL. Methods: This type of research is an experimental study using pretest-posttest with control group design. As many 24 male white rats (Rattus norvegicus L.) induced with egg yolk 6.25gr/kgBB, grouped into 4, negative controls have given with only aquadest, positive controls only given egg yolks, one treated with tomato juice 30 ml/kg body weight and two treatments given 30 ml/kg of fresh guava juice for 2 weeks which then performed blood sampling for 3 times, pretest, intervention, and posttest. Results: The mean LDL levels of negative control group posttest, positive control, one treatment and two treatments were respectively 68,66 mg / dl, 145,50 mg / dl, 71,41 mg / dl, 36,08 mg / dl. ANOVA test results showed that there was a significant difference between treatment group one and treatment group two with p = 0,016 (p <0,05). Conclusion: The administration of tomato juice and red guava juice can lowering LDL levels of mice. Red guava juice is more effective at lowering LDL concentration of mice with p = 0,001 (p <0,05) compared with tomato juice with p-value = 0,024 (p <0,05). Keywords: Cardiovascular Disease, LDL, Lycopene, Tomato Fruit Juice, Guava Fruit Juice.